THE ROLE OF THE STATE IN EFFORTS TO PROTECT CHILDREN'S RIGHTS FROM THE PERSPECTIVE OF LAW NUMBER 35 OF 2014 CONCERNING CHILD PROTECTION - Muhammad Iqbal Anwar; T. Riza Zarzani; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
This study aims to analyze the role of the state in protecting children's rights based on Law Number 35 of 2014 concerning Child Protection (UU PA). The research method used is library research with a qualitative approach and content analysis techniques. Data were obtained from literature studies on laws and regulations, policy documents, and previous research results related to child protection. The results of the study show that the state has a central role in ensuring the fulfillment of children's rights through three main aspects: regulation, policy implementation, and law enforcement. The Child Protection Law mandates the state to ensure the rights of survival, growth and development, protection from violence and discrimination, and children's participation. However, implementation in the field still faces serious challenges, such as the high number of cases of violence against children (molestation, abuse, bullying), limited access to education and health, and weak coordination between institutions. KPAI data (2023) shows an increase in cases of violence against children by 15% in the last three years, which indicates that the role of the state is not yet optimal. This study also identified that the Child Protection Act has not been fully effective due to the unclear monitoring mechanism, low budget allocation, and a permissive community culture towards violence. On the other hand, partial success is seen in the implementation of restorative justice and diversion in the juvenile criminal justice system, which reduces stigmatization of juvenile perpetrators of crimes. The conclusion of the study emphasizes the importance of strengthening regulations to strengthen sanctions for perpetrators of child crimes, increasing cross-sector synergy (government, community, non-governmental organizations), and massive education on children's rights. Strategic recommendations include the establishment of an integrated reporting system, increasing the capacity of law enforcement officers, and optimizing the role of local governments in the Child-Friendly Regency/City program.